Students Response toward the Implementation of Minecraft Education Edition in Writing as the Game Based Learning in Senior High School - Salsabila, Devina Dinar (RETAIN : Journal of Research in English Language Teaching, 2023)
The Covid-19 pandemic that has been felt by the whole world for more than 2 years has an impact on all factors, and one of them is education. Accompanied by technological advances, learning activities can be carried out remotely. But another impact of technological advances in the field of education is the emergence of boredom and students' enthusiasm for learning decreases. This has prompted researchers to conduct this research, by implementing Minecraft Education Edition as a Game-based Learning tool in learning to write, where students learn directly using games. This research was conducted to identify the student responses and student outcomes after the implementation of Game-based Learning using Minecraft Education Edition. The participants used in this study were 35 students  SMAN 16 Surabaya who are in class tenth grade MIPA 8 students as participants. The researcher used a qualitative descriptive design method in collecting data. Data were collected and analyzed by making observations during the teaching and learning process and interviews. Therefore, the researchers used observation sheet instruments, student assignments, and interview guides. The results of this study indicate that the implementation of Minecraft Education Edition as a Game-Based Learned to teach writing especially narrative writing in the classroom was effective. This was evidenced not only from student responses but also from student work which shows good results.